Broadband 75–85 MHz radiofrequency fields disrupt magnetic compass orientation in night-migratory songbirds consistent with a flavin-based radical pair magnetoreceptor - Leberecht, B; Kobylkov, D; Karwinkel, T; Doge, S; Burnus, L; Wong, SY; Apte, S; Haase, K; Musielak, I; Chetverikova, R; Dautaj, G; Bassetto, M; et al. (Springer, 2022)
The light-dependent magnetic compass sense of night-migratory songbirds can be disrupted by weak radiofrequency fields. This finding supports a quantum mechanical, radical-pair-based mechanism of magnetoreception as observed for isolated cryptochrome 4, a protein found in birds’ retinas. The exact identity of the magnetically sensitive radicals in cryptochrome is uncertain in vivo, but their formation seems to require a bound flavin adenine dinucleotide chromophore and a chain of four tryptophan residues within the protein. Resulting from the hyperfine interactions of nuclear spins with the unpaired electrons, the sensitivity of the radicals to radiofrequency magnetic fields depends strongly on the number of magnetic nuclei (hydrogen and nitrogen atoms) they contain. Quantum-chemical calculations suggested that electromagnetic noise in the frequency range 75–85 MHz could give information about the identity of the radicals involved. Here, we show that broadband 75–85 MHz radiofrequency fields prevent a night-migratory songbird from using its magnetic compass in behavioural experiments. These results indicate that at least one of the components of the radical pair involved in the sensory process of avian magnetoreception must contain a substantial number of strong hyperfine interactions as would be the case if a flavin–tryptophan radical pair were the magnetic sensor.